IMPLEMENTATION OF KNOWLEDGE MANAGEMENT IN ENHANCING TEACHERS’ COMPETENCE AT ISLAMIC JUNIOR HIGH SCHOOLS (MADRASAH TSANAWIYAH): A RECENT LITERATURE REVIEW - Dedy Yusuf Aditya; Ai Solihah; Siti Julaeha; Gita Kencanawaty (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to analyze the strengthening of knowledge management to enhance teacher engagement toward the organization at MTs Darussa’adah Pandeglang. Knowledge management is regarded as a crucial strategy for developing a sustainable learning culture within Islamic schools. The study employs a qualitative descriptive approach through literature review and field observation. The findings reveal that the key dimensions of knowledge management—creation, storage, sharing, and application of knowledge—significantly contribute to improving teachers’ involvement in organizational activities and instructional innovation. Moreover, leadership support and collaboration among teachers within professional learning communities strengthen motivation and a sense of belonging to the institution. The study recommends implementing a digital collaboration platform to facilitate knowledge sharing and foster a learning organization culture in the madrasa context.